The virtue of chastity, for the understanding of the meaning of human sexuality - Cuyate Reque, Jesús Simón (2019)
The present essay found the problem about the distortion of the true meaning of sexuality, so that, in order to solve this situation, it raises the thesis, of being the virtue of chastity, the means for understanding the meaning of sexuality human, detailing a conceptual framework on what sexuality, chastity consists of and justifying why it allows us to deepen the meaning of our sexuality.Concluding that the experience of the virtue of chastity allows us to understand the sense of sexuality towards love, from personal integrity and from the way of being male or female